An analysis of the dynamics of investment saving and economic growth in Turkey: 1950-2004 - (:unkn) unknown (My University, 2007)
0

Main aim of this study is to investigate the interaction among the saving, investment and growth in order to find out which variable is the key in terms of the causality, impulse-response from one to another. If we find out this relationship among the saving, investment and growth then we can design efficient economic policies in order to achieve an economy in which saving, investment and growth affect one to another positively. We mainly focused on Turkey which has been erratic growth performance for years. The macro economic policies of Turkey have been directed by internal and external dynamics. In this context, it becomes necessary to reassess the growth performance. Explaining the underlying sources of the economic growth of Turkey is very important not only for testing different theoretical growth models but also to design economic policies and reforms for these countries. The methodology we applied depends on the time series econometric techniques which include analyzing the stationarity of the variables, cointegration, vector error correction mechanism, and Granger causality and vector auto regressive models with impulse-response and variance decomposition techniques. We analyze the period of 1950-2004.
Keywords: Davranış Bilimleri; İş; İşletme Finans; İktisat; Tarih; Beşeri Bilimler; Uluslararası İlişkiler; İşletme; Siyasi Bilimler; Kamu Yönetimi; Sosyal Çalışma